Human skin region detection in Web video - GUO Jun-bo1; ZHANG Dong-ming1; ZHANG Yong-dong1; XU Jie1; WANG Wen-ying1 (Tongxin xuebao)
An improved detection algorithm was presented.Firstly,an improved skin color model,which adopted many preprocessing including optical offset,auto white balance,and auto gamma correction,was built to detect candidate skin pixels.Secondly,the image was filtered with erosion and dilation to exclude unconnected candidate pixels.Lastly,gray co-matrix was used to exclude those candidate human skin regions with complex texture.Experimental results show that this algorithm improves the skin region detection precision.